Sensations, mixtures and plasticity: when children experience and discover contemporary art (Revista Apotheke, 2019)
This article aims to discuss the approaches of children to contemporary art in school contexts pointing to possibilities of propositions that foster this meeting.
Keywords: child education; contemporary art; children